2018
DOI: 10.1038/s41598-018-19250-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Tree Species Diversity in Unlogged and Selectively Logged Malaysian Forests

Abstract: Selective logging that is commonly conducted in tropical forests may change tree species diversity. In rarely disturbed tropical forests, locally rare species exhibit higher survival rates. If this non–random process occurs in a logged forest, the forest will rapidly recover its tree species diversity. Here we determined whether a forest in the Pasoh Forest Reserve, Malaysia, which was selectively logged 40 years ago, recovered its original species diversity (species richness and composition). To explore this,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 34 publications
2
9
0
1
Order By: Relevance
“…Notwithstanding, regrowth forests being useful in conservation of woody species, they do not, however, harbour the full suite of species found in old-growth-forests, particularly the dispersal limited late-successional species. Furthermore, old-growth forests tend to contain relatively more rare species as found in this and previous studies (Brunialti et al 2010;Ngo and Hölscher 2014;Shima et al 2018). The structural heterogeneity of old-growth forests, which is manifested by high tree height and diameter class variations and higher number of strata, provides niches for various species (McElhinny et al 2005;Gao et al 2014).…”
Section: Floristic Diversity and Compositionsupporting
confidence: 59%
“…Notwithstanding, regrowth forests being useful in conservation of woody species, they do not, however, harbour the full suite of species found in old-growth-forests, particularly the dispersal limited late-successional species. Furthermore, old-growth forests tend to contain relatively more rare species as found in this and previous studies (Brunialti et al 2010;Ngo and Hölscher 2014;Shima et al 2018). The structural heterogeneity of old-growth forests, which is manifested by high tree height and diameter class variations and higher number of strata, provides niches for various species (McElhinny et al 2005;Gao et al 2014).…”
Section: Floristic Diversity and Compositionsupporting
confidence: 59%
“…Mohammadi et al (2008) and Awasthi et al (2015) also found a decrease in the species diversity where Shelterwood Silvicultural System was practiced in the natural forest stands, similar to the results obtained. The species composition and diversity are related to the intensity of logging and type of management practices (de Avila et al 2015), which means the higher the harvesting intensity the lower the species diversity in SciFM practices (Shima et al 2018;Awasthi et al 2020). Halpern and Spies (1995) also found other management activities (fertilization, herbicide application, grazing) could affect the species composition of vegetation in addition to the initial effect of logging and site preparation.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to assess the stand dynamics of disturbed tropical forests, comparative information on the changes in size structure, species composition, and demographic processes, such as growth, mortality, and recruitment, has been obtained [9][10][11][12][13]. These studies used data between two censuses at different periods or between disturbed and undisturbed control plots.…”
Section: Introductionmentioning
confidence: 99%